Bersama dalam Penderitaan - Harjito Harjito (MAJALAH LONTAR, 2007)
The aim of the writing t find the problem in the text of dangdut songs “Gbug Derita” and “Sepiring Berdua”. The  methods of the research is library reseach. The conclusion of the stdi is text in “Gubug Derita” and “Sepiring Berdua” tell us about the mortal love and broken heart that occurs in people of low class society. They always surrender in they life / dignity. This case indentifies that the reality of people in low class society do not have a wish to change their life or dignity but they just accept is as their life Keywords: suffering, dignity